Scream [videorecording (DVD)] - Craven, Wes; Arquette, David; Campbell, Neve, 1973-; Cox, Courteney, 1964- (Paramount, 2021)
A year after her mother's death, Sidney Prescott and her friends become the targets of a serial killer.